Cyclodextrins as excipients in tablet formulations. Issue 6 (June 2018) - Conceição, Jaime; Adeoye, Oluwatomide; Cabral-Marques, Helena Maria; Lobo, José Manuel Sousa
Highlights: Cyclodextrins are complexing excipients in tablets mainly for potent drugs. Methods to enhance the complexation efficiency decrease the cyclodextrin quantity. Inclusion complex flow properties play a crucial part in the tablet manufacture process. Commercial tablets containing cyclodextrins are available on the market. 3D-printed tablets can be developed containing cyclodextrins as excipients. Abstract : This paper aims to provide a critical review of cyclodextrins as excipients in tablet formulations, highlighting: (i) the principal pharmaceutical applications of cyclodextrins; (ii) the most relevant technological aspects in pharmaceutical formulation development; and (iii) the actual regulatory status of cyclodextrins. Moreover, several illustrative examples are presented. Cyclodextrins can be used as complexing excipients in tablet formulations for low-dose drugs. By contrast, for medium-dose drugs and/or when the complexation efficiency is low, the methods to enhance the complexation efficiency play a key part in reducing the cyclodextrin quantity. In addition, these compounds are used as fillers, disintegrants, binders and multifunctional direct compression excipients of the tablets.